The impact of Intermittent Fasting on Weight Loss and Metabolic Health - a review of the latest research - Marta Justyna Gonciarz; Dominika Karolina Adamiec; Anna Dąbrowska; Natalia Paduszyńska; Dominika Zaliwska; Magdalena Czach; Agnieszka Aleksandra Strojny; Adrianna Kraszkiewicz; Monika Anna Kamińska; Monika Kienanh Do (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose        Intermittent fasting (IF) is a dietary pattern that alternates between periods of fasting or reduced caloric intake and periods of unrestricted eating. There are three primary types of IF: Alternate Day Fasting (ADF), Time-Restricted Eating (TRE), and Periodic Fasting (PF). This review article summarizes the impact of IF on weight loss. Additionally, it examines the broader health effects of IF, including its influence on cardiovascular risk, diabetes management, and neurodegenerative diseases.    Description of the state of knowledge        Fasting, the practice of abstaining from or limiting food intake for a specified period, has been a cultural and religious tradition worldwide for centurie. Common IF methods alternating 24-hour periods of fasting with days of eating, TRE restricts eating to specific windows of time each day, and PF includes patterns such as the 5:2 diet, where fasting occurs on two days each week.   Conclusions        The analysis of the review article demonstrates that intermittent fasting (IF) leads to weight loss, aiding in the treatment of obesity. Moreover, IF reduces glycated hemoglobin levels and increases periods of normoglycemia, potentially benefiting diabetes patients. Nonetheless, there is a lack of sufficient research to confirm the safety of IF for diabetics, given the risk of hypoglycemia. Research also indicates that IF positively impacts cardiovascular risk factors by lowering total cholesterol, LDL-C, and triglyceride levels. Additionally, while IF might reduce the risk of certain cancers by addressing obesity, it is not advised for cancer patients due to inadequate scientific evidence. Furthermore, some studies indicate that IF could be advantageous in managing certain neurological diseases.